ANALISIS FAKTORâFAKTOR YANG MEMPENGARUHI TAX COMPLIANCE WAJIB PAJAK BADAN (Studi Empiris Pada Tax Profesional Perusahan Industri Yang Terdaftar Di Kantor Pelayanan Pajak Pratama Semarang Gayamsari) - Nova Ariantono, 10.05.52.0148; Kartika, Andi (Students Journal of Accounting and Banking, 2015)
The purpose of this study was to determine the influence of attitudes, intentions financial condition, corporate facilities and organizational climate on tax compliance bodies in industrial companies registered at the Tax Office Primary Gayamsari Semarang. The population of this study is the tax professionals who work in medium and large industrial companies registered at the Tax Office Primary Gayamsari Semarang. The sample used incidental sampling technique produced by 80 respondents. The method of data analysis using multiple linear regression analysis. Based on data analysis can be seen attitudes, intentions, financial condition, corporate facilities and organizational climate and the company has a significant positive effect simultaneously on corporate tax compliance.Keywords: Knowledge of Tax, Tax Fairness, Adherence, Companyâs Tax Compliance